2005
DOI: 10.1016/j.ejvs.2005.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Elective Open Operation for Abdominal Aortic Aneurysm in Octogenarians—Survival Analysis of 105 Patients

Abstract: The number of AAA operations in octogenarians has increased considerably during 20 years. Octogenarians operated electively for AAA has higher 30-day mortality as compared to younger patients. Their long-term survival appears similar to a matched control group. The benefit of surgery must be carefully considered against the perioperative risk, especially for the oldest octogenarians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 29 publications
3
25
1
3
Order By: Relevance
“…8,9 Operative mortality in octogenarians is reported to range from 5.7% to 10.5%. 5,8,9 In the present series, the prognosis of patients treated nonoperatively deteriorated once the AAA diameter had reached a critical point of 6 cm. Of the 23 octogenarians with an AAA smaller than 6 cm in diameter, 12 died; none of rupture.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…8,9 Operative mortality in octogenarians is reported to range from 5.7% to 10.5%. 5,8,9 In the present series, the prognosis of patients treated nonoperatively deteriorated once the AAA diameter had reached a critical point of 6 cm. Of the 23 octogenarians with an AAA smaller than 6 cm in diameter, 12 died; none of rupture.…”
Section: Discussionmentioning
confidence: 56%
“…There are many reports on AAA surgery in octogenarians, but most focus on the safety of surgery in relation to patients undergoing AAA operations. 4,5,7 There are few papers discussing the prognosis of patients treated nonoperatively or operatively, as in the present study. 8,9 Operative mortality in octogenarians is reported to range from 5.7% to 10.5%.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…With respect to AAA patients in good anatomical condition, endovascular aortic repair (EVAR) has become the first choice in place of traditional open operations. Although several studies have revealed that the mortality rate and incidence of complications in patients aged 80 years and older during the operation period and in the medium to long term were higher than those of younger patients, almost all authors have indicated that if preoperative evaluations are conducted, the results of EVAR technology would nonetheless be satisfactory (Brinkman et al, 2004;Haug et al, 2005;Henebiens et al, 2008). Therefore, for symptomatic AAA patients aged 90 or older, decision-makers should primarily focus on the risk of repair and on subjective issues related to life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Limited functional reserve of octogenarians has stimulated the use of minimally invasive techniques, mainly endovascular aneurysm repair (EVAR). [7][8][9][10][11][12][13][14] However, direct aortic repair (DAR) with aneurysmorraphy and bypass graft interposition remains a reliable and suitable alternative in selected octogenarians.…”
mentioning
confidence: 99%